The Merck/Merial manual for pet health - Kahn, Cynthia M.; Line, Scott; Merck & Co.; Merial (Firm) (Whitehouse Station, NJ : Merck & Co., 2007)
An in-depth reference for pet owners addresses a full spectrum of caregiver concerns for dogs, cats, horses, birds, and exotics, from selecting a compatible animal companion to coping with a range of diseases and disorders.--Source other than Library of Congress.
Dog basics -- Disorders and diseases of dogs -- Cat basics -- Disorders and diseases of cats -- Horse basics -- Disorders and diseases of horses -- Birds -- Exotic pets -- Special subjects.
Fakulti Peubatan Vererinar.
Includes index.
Keywords: Animal health -- Handbooks, manuals, etc; Pets -- Diseases -- Handbooks, manuals, etc; Pets -- Health -- Handbooks, manuals, etc